Manajemen pendistribusian zakat fitrah dalam upaya penanggulangan kemiskinan: Studi kasus di Desa Campor Barat Kecamatan Ambunten Kabupaten Sumenep - Jannah, Rumanatul (Maliki Interdisciplinary Journal, 2024)
Zakat is a responsibility that must be completed for every Muslim who is classified as well-off. Zakat is one of the enormous potentials in alleviating poverty in Indonesia, especially with Islam as the majority religion in Indonesia. The distribution of zakat immediately or circuitously is one of the existing troubles. As occurred in West Campor Village, Ambunten District, Sumenep Regency. This studies uses a field research type method. The way to attain statistics within the area thru interviews. The effects of this have a look at display that the distribution of zakat in West Campor Village continues to be very suboptimal, this is due to the fact within the distribution method there's nonetheless no data series and nonetheless the use of two approaches of distributing zakat, this causes many mustahik to be missed or do now not receive their rights. The role of community leaders as amil zakat within the village is accurate, however more seriousness remains needed so they mustahik aren't missed for the duration of the zakat distribution system, then with zakat must additionally be able to help mustahik to elevate their fashionable of dwelling, the only manner to do this is through distributing zakat the usage of the technique of distributing zakat prosductively, this type of distribution could be very powerful in overcoming current poverty issues with the aid of utilising zakat as a source of help, with this type of zakat zakat is distributed no longer inside the shape of consumptive distribution, but capital or equipment that can support their day by day work.